Keys to success : building analytical, creative, and practical skills - Carter, Carol (Pearson Prentice Hall, 2009)
The Keys message is simple – When students understand how material will help them get where they want to go, they will become more motivated and able to retain what they learn. Because this text shows readers how what helps them succeed in colllege will also serve them on the job and in life, Keys to Success, appeals to every age (traditional and older) and stage (full-time, part-time, working, parenting) of student.